Distinguishing ionospheric scintillation from multipath in GNSS signals using geodetic receivers - Li, Chendong (2022)
Ionospheric scintillation is an important phenomenon affecting GNSS positioning accuracy. Scintillation parameters, S4 and σφ, are usually used to characterize scintillation in amplitude and phase, respectively. S4 and σφ can be contaminated by multipath effects in certain circumstances. Similarly, the multipath parameter (MP) can also be affected by scintillation. Therefore, it is difficult to distinguish whether an increase in the scintillation parameters and MP is caused by scintillation or multipath. However, it is important to know the type of interference to apply appropriate mitigation measures. It is known that the multipath effect is periodic as compared to scintillation if the receiver location is fixed. Based on this peculiar feature, this article proposes to use parameters MP, S4, σφ and the rate of change of total electron content index (ROTI) characterize the receiver station surroundings so that multipath and scintillation effects can be distinguished. The Global Positioning System (GPS) data for two one-month records at two pairs of low-latitude stations, namely SAO0P-SJCU and SJCU-SJCE, located in Sao Paulo, Brazil, were used to generate elevation layered plots and parameter values against elevation and azimuth (PEA) plots for each satellite on each day. The second station was used as a reference for validating the conclusion. The results provide evidence that the proposed methodology can identify all multipath, scintillation and hybrid (of multipath and scintillation) events using scintillation indices and identify some multipath, scintillation and hybrid events using MP and ROTI. For hybrid events below 30° elevation, this methodology is not effective.